El Centro Integrado Maricarmen y la importancia de crear cultura de calidad en instituciones que aprenden - Ramírez Talledo, Patricia Milagros (2011)
The present article is aboutthe educational qualityfrom the developing experience in Maricarmen's Inclusive School. The significant learning applies useful strategies and the knowledge efficacy allows the student to inte'act with their classmates and their environment during the learning process, which benefits are verified in several areas ofthe reality and in particular inthe individual.